2013
DOI: 10.14569/ijarai.2013.021207
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Software Effort Estimation Models Using Multigene Symbolic Regression Genetic Programming

Abstract: Abstract-Software has played an essential role in engineering, economic development, stock market growth and military applications. Mature software industry count on highly predictive software effort estimation models. Correct estimation of software effort lead to correct estimation of budget and development time. It also allows companies to develop appropriate time plan for marketing campaign. Now a day it became a great challenge to get these estimates due to the increasing number of attributes which affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although some studies have used log-transformed variables (e.g., , Jeffery et al [2000], Chen et al [2005], and Dejaeger et al [2012]), Jorgensen and Shepperd [2007] found that few studies look at the "properties of the data." Although the warnings from Kitchenham and Mendes [2009], were presented some years ago, it appears that the trend in applying linear models without a consideration of the data and model assumptions has continued [Bardsiri et al 2014], or that no comparison against other models or the use of a training/test comparison is even considered [Aljahdali and Sheta 2013]. In response, in recent years increasing attention has been directed to the need for baseline models in SEE, against which any newly proposed model should be positively compared before adoption and use, that is, the new model should be shown superior to the baseline model.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have used log-transformed variables (e.g., , Jeffery et al [2000], Chen et al [2005], and Dejaeger et al [2012]), Jorgensen and Shepperd [2007] found that few studies look at the "properties of the data." Although the warnings from Kitchenham and Mendes [2009], were presented some years ago, it appears that the trend in applying linear models without a consideration of the data and model assumptions has continued [Bardsiri et al 2014], or that no comparison against other models or the use of a training/test comparison is even considered [Aljahdali and Sheta 2013]. In response, in recent years increasing attention has been directed to the need for baseline models in SEE, against which any newly proposed model should be positively compared before adoption and use, that is, the new model should be shown superior to the baseline model.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm evolves these genes through genetic operations such as mutation, crossover, and selection, seeking to optimize the fitness function, which measures how well the set of genes fits a given dataset. MG-GP has been known to be a powerful tool for solving complex regression problems, such as those found in modeling and optimization of manufacturing processes [36], [37], software effort estimation [38], image reconstruction [39], and many others [40], [41]. It can address problems with datasets that have a complex and noisy relationship.…”
Section: What Is Multigene Symbolic Regression Gp?mentioning
confidence: 99%
“…Their results showed that parameter tuning can have critical impact on algorithmic performance, and that overfitting of parameter tuning is a serious limitation of empirical studies in search-based software engineering. In (Aljahdali and Sheta 2013), the authors argued that recently, computational intelligence paradigms were explored to handle the software effort estimation problem with promising results. In this paper they evolve two new models for software effort estimation using Multigene Symbolic Regression Genetic Programming.…”
Section: Effort Prediction Approaches Using Genetic Algorithmsmentioning
confidence: 99%